1986
DOI: 10.1182/blood.v67.2.391.bloodjournal672391
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin gene rearrangements and expression in diffuse histiocytic lymphomas reveal cellular lineage, molecular defects, and sites of chromosomal translocation

Abstract: We have examined the immunoglobulin gene configurations in cell lines from eight patients with diffuse histiocytic lymphoma in order to establish the cellular lineage and stage of differentiation of these lymphomas. The presence of heavy and light chain gene rearrangements as well as heavy chain class switching in seven cells placed these tumors within the B cell lineage. In contrast, one cell (SU-DHL-1), which lacks B cell-restricted surface antigens, retained germline heavy and light chain loci, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous gene expression profiles of diffuse large B‐cell lymphoma (DLBCL) cell lines demonstrated that both cell lines display similar molecular signatures, and cluster together with a ‘germinal centre‐derived’ phenotype rather than an ‘activated B‐cell type’ or ‘type3’ phenotype (Rosenwald et al , 2002). Both cell lines also carry the t(14;18) translocation involving the immunoglobulin heavy chain locus and bcl‐2 (Bakhshi et al , 1985; Siminovitch et al , 1986). SUDHL‐4 and SUDHL‐6 cell lines therefore represent a good model system to identify markers that account for their differential response to proteasome inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous gene expression profiles of diffuse large B‐cell lymphoma (DLBCL) cell lines demonstrated that both cell lines display similar molecular signatures, and cluster together with a ‘germinal centre‐derived’ phenotype rather than an ‘activated B‐cell type’ or ‘type3’ phenotype (Rosenwald et al , 2002). Both cell lines also carry the t(14;18) translocation involving the immunoglobulin heavy chain locus and bcl‐2 (Bakhshi et al , 1985; Siminovitch et al , 1986). SUDHL‐4 and SUDHL‐6 cell lines therefore represent a good model system to identify markers that account for their differential response to proteasome inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the pseudo-JH3 gene in case 7 may be an example of inactivation of one IgH allele by t (14 ;18) and the other by nonfunctional rearrangement leading to defective Ig production . Indications for defects in transcription were given by Siminovitch et al (15), who described several diffuse B cell lymphoma cell lines without Ig H chain expression, in which one or both H chain alleles were rearranged . Truncated Ig H and L chain mRNAs were seen on Northern blots in one case, suggesting transcriptional defects (15).…”
Section: Discussionmentioning
confidence: 99%
“…Indications for defects in transcription were given by Siminovitch et al (15), who described several diffuse B cell lymphoma cell lines without Ig H chain expression, in which one or both H chain alleles were rearranged . Truncated Ig H and L chain mRNAs were seen on Northern blots in one case, suggesting transcriptional defects (15). The contribution ofother possible mechanisms in defective Ig production may be revealed by cloning and sequencing of IgH alleles in Igtumors and needs further research .…”
Section: Discussionmentioning
confidence: 99%
“…The human DLBCL cell lines, OCI‐LY1 and SU‐DHL‐2, were available in our laboratory in SYSUCC. The cell lines were cultured in RPMI 1640 medium with 10% EV‐free fetal bovine serum (FBS) and 1% Pen‐Strep at 37°C under 5% CO 2 (RPMI 1640, FBS and Pen‐Strep were from Gibco).…”
Section: Methodsmentioning
confidence: 99%